Effectiveness of the Border Crossing Post in Monitoring the Mobility of Illegal Migrant Workers: An Analysis of Challenges and Obstacles in the Indonesia-Malaysia Border Region - Alus Alus; Eny Haryati; Ika Devy Pramudiana (International Forum of Researchers and Lecturers, 2026)
The Kalimantan border region, which directly adjoins Malaysia, faces a serious problem: the mobility of Indonesian Migrant Workers (PMI) departing through nonprocedural channels remains high, whether through the Border Crossing Post (PLBN) or unofficial routes. Official data record at least 70 unofficial paths in West Kalimantan, while North Kalimantan shows a recurring pattern of deportation. This condition raises the question of how effectively the PLBN performs its supervisory function. This study analyzes the effectiveness of the PLBN in monitoring illegal PMI mobility and identifies the challenges and obstacles faced by supervisory personnel along the Indonesia-Malaysia border. The population comprised border-supervision stakeholders at PLBN Entikong and PLBN Badau in West Kalimantan, and PLBN Sei Pancang and Nunukan in North Kalimantan. The sample consisted of ten purposively selected informants, including PLBN officers, Immigration Office staff, BP3MI officials, the Army's Border Security Task Force (Satgas Pamtas TNI), police, and border community leaders. Data were collected through in-depth interviews, field observation, and documentation study, and analyzed qualitatively using an interactive model in which data were condensed, displayed thematically, and then used to draw conclusions; validity was established through source and technique triangulation. The findings show that the PLBN is fairly effective in monitoring mobility on official routes; however, this effectiveness is spatial and easily circumvented, since recruitment networks can alter routes, timing, and methods of departure. The main obstacles include geographic conditions, limited resources, interagency data fragmentation, regulatory disharmony, economic pressure on border communities, and difficulty enforcing the law against key recruiters.